PEREMPUAN TANPA AYAH: QS. Luqmān (31):17 Sebagai Sumber Moral Bagi Mahasiswi Urban IAIN Pontianak - Maimunah; Syafa Safira Dwi Firdayanti; Luqman Abdul Jabbar (Universitas Muhammadiyah Jember, 2026)
The phenomenon of women growing up without a father (fatherlessness) is increasingly found in urban communities and has implications for their moral, emotional, and identity development. This study aims to examine how urban female university students in Pontianak City who experience fatherlessness construct Islamic moral values through their understanding of Qur’anic Surah Luqmān (31):17. This research employs a phenomenological approach supported by tafsīr analysis to explore how the students’ emotional, spiritual, and social experiences influence the internalization of the values of prayer (ṣalāh), enjoining good (amr maʿrūf), forbidding evil (nahy munkar), and patience (ṣabr). Data were collected through literature review, social observation, and in-depth interviews with fatherless female students. The findings reveal that the absence of a father contributes to a more independent and reflective process of moral formation. The students interpret Surah Luqmān (31):17 not merely as a normative command but as a moral guideline that shapes their daily conduct. These values help them respond to urban life challenges, manage emotions, and strengthen their personal identity. This study contributes to discussions on Islamic moral education by integrating lived experiences of fatherless female students with Qur’anic interpretation in the context of higher education and urban life.